A model of lineage-1 and lineage-2 rinderpest virus transmission in pastoral areas of East Africa - Mariner, Jeffrey C.; McDermott, John J.; Heesterbeek, J.A.P.; Catley, A.; Roeder, P. (Elsevier, 2005)
The development of a stochastic, state-transition model of rinderpest transmission dynamics is described using parameter estimates obtained from both laboratory and participatory research. Using serological data, the basic reproduction numbers for lineage-1 rinderpest virus in southern Sudan and for lineage-2 rinderpest virus in Somali livestock were estimated as 4.4 and between 1.2 and 1.9, respectively. The model predictions for the inter-epidemic period in Sudan and Somalia (1.2 and 4.2 years, respectively) were in agreement with analysis of livestock-owner reports (1-2 years and 5 years, respectively).